Prediksi Peserta Didik Baru untuk Mengoptimalkan Promosi Menggunakan Algoritma Monte Carlo - Najib, Muhammad; Roza, Faisal (SAFE-Network, 2022)
Telkom Elementary school of Padang is the digital-based school that utilizes advanced technology to elevate the quality of teaching, service, and evaluation. Digitalization is supposed to be provided with digital tools in which those are the most important things for the development of the school. This element is significantly beneficial for assisting the process of the school promotion in terms of students admission. To go further, the use of technology in this school has been incredibly beneficial for improving the promotion process of students admission. In the beginning of 2019, Telkom elementary school of Padang has been utilizing technology for obtaining the data of new students such as the information of registrants’ identity and payment process. Currently, Telkom Elementary school of Padang needs more evaluation towards its previous data that has been derived by digital tools in order to optimize the promotion process. Therefore, optimizing the promotion in students’ admission process becomes the main objective of this study. In order to achieve the goal, the data that used in this study is derived from school year off 2020-2021 and 2022-2023. The data consists of registration number, registration date, students name, and the name of the previous school that has been attended. Furthermore, Monte Carlo has been selected as the method used in this study. Based on the Monte Carlo test, there are 124 registrants predicted in the school year of 2021-2022 with the accuracy rate of 84%, 115 registrants for the school year of 2022-2023 with 81% of accuracy level, and 129 registrants predicted for the upcoming school year of 2023-2024. Thus, this research is able to be a reference for optimizing the promotion process in students admission of Telkom Elementary School of Padang.